2018
DOI: 10.3390/genes9100503
|View full text |Cite
|
Sign up to set email alerts
|

The Complete Plastome Sequences of Eleven Capsicum Genotypes: Insights into DNA Variation and Molecular Evolution

Abstract: Members of the genus Capsicum are of great economic importance, including both wild forms and cultivars of peppers and chilies. The high number of potentially informative characteristics that can be identified through next-generation sequencing technologies gave a huge boost to evolutionary and comparative genomic research in higher plants. Here, we determined the complete nucleotide sequences of the plastomes of eight Capsicum species (eleven genotypes), representing the three main taxonomic groups in the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 61 publications
(89 reference statements)
3
30
2
Order By: Relevance
“…The SSR loci were located in 31 coding genes ( matK , atpI , rpoC2 , rpoB , trnS-UGA , rps14 , psaB , psaA , ndhK , accD , ycf4 , cemA , petA, psaJ, psbB , rpoA , rpl22 , rps19 , rpl2 , ycf2 , rrn23 , ndhF , rpl32 , ccsA , ndhD , ndhA , ycf1 , trnI-GAU , ndhB , ycf2 ) and 57 intergenic regions of the 22 Lythraceae species. Yu et al found 20 SSRs located in 9 coding genes ( matK , rpoC1 , rpoC2 , cemA , ndhD , ndhG , ndhH , ycf2 and ycf1 ) of the Fritillaria cp genome [23]. These results indicate that SSRs with large variation in cp genomes can be applied to identify related species and used in research on phylogeny.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSR loci were located in 31 coding genes ( matK , atpI , rpoC2 , rpoB , trnS-UGA , rps14 , psaB , psaA , ndhK , accD , ycf4 , cemA , petA, psaJ, psbB , rpoA , rpl22 , rps19 , rpl2 , ycf2 , rrn23 , ndhF , rpl32 , ccsA , ndhD , ndhA , ycf1 , trnI-GAU , ndhB , ycf2 ) and 57 intergenic regions of the 22 Lythraceae species. Yu et al found 20 SSRs located in 9 coding genes ( matK , rpoC1 , rpoC2 , cemA , ndhD , ndhG , ndhH , ycf2 and ycf1 ) of the Fritillaria cp genome [23]. These results indicate that SSRs with large variation in cp genomes can be applied to identify related species and used in research on phylogeny.…”
Section: Resultsmentioning
confidence: 99%
“…The genes rpl2 , rpl20 and rpl23 involved in replication, rbcL and psbJ involved in photosynthesis, ycf4 of unknown functions and other genes including ccsA evolved more quickly and had high Ka/Ks (≥1). The seven genes evolved faster among 22 Lythraceae species analyzed were also found in Capsicum and Sesamum indicum species [23, 46]. Some genes are species-specific in terms of the rates of evolution, such as clpP gene.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research on the phylogenetic relationships of the three avocado ecological races based on specific length amplified fragment sequencing [18], transcriptomes examined according to single nucleotide polymorphisms [18], and transcriptomes investigated based on differentially expressed genes [19] revealed that the Mexican and Guatemalan races are more closely related to each other than to the West Indian race. Specific characteristics of chloroplast genome sequences (e.g., uniparental inheritance, low recombination, and low nucleotide substitution rates) make these sequences relevant for resolving the interspecific or intraspecific boundary, and are particularly useful for phylogenetic studies involving diverse species, including Lonicera [20], Nymphaeaceae [21], Ziziphus [22], Capsicum [23], Rosa [24], and Cruciata [25] species. However, chloroplast genomes have not been used for elucidating the phylogenetic relationships among the three avocado ecological races.…”
Section: Introductionmentioning
confidence: 99%
“…The region of the chloroplast genome around the accD gene has been found to be prone to accumulation of repeats, resulting in high interspecific variability in numerous species ( Pisum and Lathyrus [45], Capsicum [54], Glycine [43], Silene [47], Oenothera [55,56], Cupressophytes [57]) but much less variability at the intraspecific level ( Medicago truncatula [44], tea, Camellia sinensis [58], and pea, Pisum sp . [39,40]).…”
Section: Discussionmentioning
confidence: 99%